In Vitro Starch Digestibility of Commercial Gluten‐Free Pasta: The Role of Ingredients and Origin. Issue 4 (8th March 2017) - Marti, Alessandra; Abbasi Parizad, Parisa; Marengo, Mauro; Erba, Daniela; Pagani, Maria Ambrogina; Casiraghi, Maria Cristina
Abstract: Gluten replacement in gluten‐free (GF) products presents major challenges for the food industry in terms of sensorial, technological and nutritional characteristics. The absence of gluten reportedly affects starch digestibility, thus increasing the postprandial glycaemic response. However, the role of ingredients and processing conditions has been addressed only seldom. We investigated the in vitro starch digestibility of 9 commercial GF products (5 Italian pasta and 4 Oriental noodles) differing in formulation and processing conditions. Content of rapidly digestible starch (RDS), slowly digestible starch (SDS), and resistant starch (RS) were assessed and combined with information on starch pasting properties and on the overall protein organization. Oriental noodles presented higher relative levels of RS and RDS than Western‐style pasta, that often had SDS levels compatible with low rates of starch digestion. As regard formulation, presence of multiple ingredients seems to likely increase the RDS level, as did the different protein organization in the various samples.